2008
DOI: 10.1242/dev.018986
|View full text |Cite
|
Sign up to set email alerts
|

BMP antagonism is required in both the node and lateral plate mesoderm for mammalian left-right axis establishment

Abstract: In mouse, left-right (L-R) patterning depends on asymmetric expression of Nodal around the node, leading to Nodal expression specifically in the left lateral plate mesoderm (LPM). Bone morphogenetic protein (BMP) signaling is also involved, but the mechanistic relationship with Nodal expression remains unclear. We find that BMP signal transduction is higher in the right LPM, although Bmp4, which is required for L-R patterning, is expressed symmetrically. By contrast, the BMP antagonists noggin (Nog) and chordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 48 publications
3
54
0
Order By: Relevance
“…BMPs have been implicated in LR patterning, but data on their precise roles have been highly contradictory, with results varying both within and between developmental models Yokouchi et al 1999;Monsoro-Burq and Le Douarin 2001;Fujiwara et al 2002;Piedra and Ros 2002;Schlange et al 2002;Kishigami et al 2004;Zhu and Scott 2004;Chocron et al 2007;Mine et al 2008). This is in part because BMPs act at distinct times and in distinct spatial domains to influence laterality (Kishigami et al 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…BMPs have been implicated in LR patterning, but data on their precise roles have been highly contradictory, with results varying both within and between developmental models Yokouchi et al 1999;Monsoro-Burq and Le Douarin 2001;Fujiwara et al 2002;Piedra and Ros 2002;Schlange et al 2002;Kishigami et al 2004;Zhu and Scott 2004;Chocron et al 2007;Mine et al 2008). This is in part because BMPs act at distinct times and in distinct spatial domains to influence laterality (Kishigami et al 2004).…”
mentioning
confidence: 99%
“…This is in part because BMPs act at distinct times and in distinct spatial domains to influence laterality (Kishigami et al 2004). Genetic data have provided evidence that BMPs need to be inhibited for correct left-sided Nodal expression (Chang et al 2000(Chang et al , 2002Constam and Robertson 2000;Kishigami et al 2004;Mine et al 2008). However, the spatial and temporal requirement for BMP signaling in these models could not be precisely established as both the node and the LPM were affected, casting doubt on the integrity of nodal flow and/or the midline barrier.…”
mentioning
confidence: 99%
“…In a recent study, it was demonstrated that BMP antagonism is required for the L-R asymmetrical Nodal expression in the mouse LPM (Mine et al, 2008). This distinct molecular regulation of Nodal expression between the chick and mouse could be attributed to species difference, as it has been demonstrated previously for the role of Shh and Fgf8 in the determination of L-R axis determination (Myers and Martin, 1999).…”
Section: Bmp Is Necessary and Sufficient To Induce Nodal Expression Imentioning
confidence: 63%
“…In mice, although studies argued for a possible role for BMP signaling in the regulation of Nodal expression in the LPM (Fujiwara et al, 2002), many studies pointed to a negative role for BMP in Nodal induction (Chang et al, 2000;Kishigami et al, 2004;Mine et al, 2008). In a recent study, it was demonstrated that BMP antagonism is required for the L-R asymmetrical Nodal expression in the mouse LPM (Mine et al, 2008).…”
Section: Bmp Is Necessary and Sufficient To Induce Nodal Expression Imentioning
confidence: 99%
See 1 more Smart Citation